A SYSTEMATIC OVERVIEW ON PARPATI KALPANAS - Sushant, Sud; Srinivasulu, Bandari (International Journal of Ayurveda and Pharma Research, 2015)
Rasa Shastra (science of alchemy) deals with Parada (mercury) and it is considered to be the heart of Rasa Shastra. In fact, the whole science is under the influence of physical and chemical properties of Parada. Rasa Shastra, one of the Pharmaco-therapeutic branches of Ayurved, incorporates many of the Herbo-mineral-metallic pharmaceutical preparations prepared out of the Parada namely Khalviya Rasayana [medicine is prepared grinding the ingredients in a Khalva Yantra (comparable with mortar and pestle)], Parpati Rasayana (thin flake like medicines), Pottali Rasayana (medicines prepared in cloth) and Kupipakwa Rasayana (Medicines prepared in bottle) respectively. The Historical evidences of Parpati Kalpana ways back in the 11th Century having references from Chakradatta written by Acharya Chakrapani. The term Parpati (thin flake like medicine) has been used in many context of Rasa Shastra. Parpati is a thin Flake like preparation consisting of Parada, Gandhaka (sulphur) and other drugs which are developed from Parada. This Preparation of Parada consist therapeutically effective minerals and metallic formulations which includes both Sagandha (with sulphur) and Nirgandha (without sulphur) Parada Murchita Yoga (medicines prepared out of mercury). Parpati Rasayanas have high therapeutic value, potency, less toxicity and cost effective preparations. Many works have been done on Parpati related to its pharmaceutical, clinical and literary part but so far, there is no work on Parpati Kalpana. Considering detailed review on Pharmaceutical and Analytical Parameters applicable for Parpati preparations. So, in this paper an honest attempt has been made to have a systematic overview of Parpati Kalpanas.